Profitability as an Intervening Variable in the Effect of Capital Structure and Firm Size on Firm Value - Fatih Fajrin Faridi; Nuradiansyah Pamungkas; Tri Neliana (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of capital structure and firm size on firm value, with profitability serving as an intervening variable. The research is motivated by inconsistencies in previous findings regarding the relationship between capital structure, firm size, and firm value. Using a quantitative approach and secondary data from selected companies, the analysis was conducted through path analysis to evaluate both direct and indirect effects. The results indicate that capital structure and firm size significantly influence firm value, both directly and indirectly through profitability. Profitability is found to play a mediating role, reinforcing the importance of internal performance metrics in enhancing firm value.